Removable Partial Denture Education in U.S. Dental Schools - Vicki C. Petropoulos, DMD, MS1 and Behnoush Rashedi, DMD, MSEd, MS2 (Journal of Prosthodontics, 2006)
Asurvey of U.S. dental schools was conducted in 2001 to determine the curricular structure, techniques, and materials used in predoctoral clinical removable partial denture (RPD) programs.